(untitled) (ModaPalavra e-periódico, 2015)
The historical and cultural trajectory of the Brazilian textile sector and clothing industry shows that there was and still is a process of change. With the opening of the trade market, which brought the globalization of the domestic market, the sector suffered a structural shock, moreover, Brazil is experiencing an invasion of Asian imports. On the other hand, the Brazilian textile industry trajectory has a history of about 200 years with cases of success and failure at different times of crises, as well as other countries in Europe, North America and Asia. China currently appears as the world leader in exports of textile and apparel products. The impacts of the Chinese economic expansion over the Brazilian textile industry begin to be felt. In the history of the Brazilian textile industry, we can emphasize technology as a strategic factor for change and development, including the subject of fashion, which currently requires adherence to technological complexity due to the need to assimilate new artistic and cultural trends for continuous redefinition of culture and even of individuality.